2021
DOI: 10.18632/aging.203600
|View full text |Cite
|
Sign up to set email alerts
|

Development of infrastructure for a systemic multidisciplinary approach to study aging in retired sled dogs

Abstract: Canines represent a valuable model for mammalian aging studies as large animals with short lifespans, allowing longitudinal analyses within a reasonable time frame. Moreover, they develop a spectrum of aging-related diseases resembling that of humans, are exposed to similar environments, and have been reasonably well studied in terms of physiology and genetics. To overcome substantial variables that complicate studies of privately-owned household dogs, we have focused on a more uniform population composed of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…The high sensitivity and specificity of ELISA were indicated by the detection of IgM antibodies and comparison of tested sera results with IgG antibodies. Immunological resistance and sensitivity of a dog to canine distemper virus are multifactorial, and the predictive value of antibody-responses or antibody-titers can be challenging due to variations in strain virulence, infective viral dose, adequacy of helper T cell-mediated immunity, immune-mediated cytotoxicity, and the persistence of memory cells [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity and specificity of ELISA were indicated by the detection of IgM antibodies and comparison of tested sera results with IgG antibodies. Immunological resistance and sensitivity of a dog to canine distemper virus are multifactorial, and the predictive value of antibody-responses or antibody-titers can be challenging due to variations in strain virulence, infective viral dose, adequacy of helper T cell-mediated immunity, immune-mediated cytotoxicity, and the persistence of memory cells [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morgan et al’s morphologic and mobility trials also assessed timed stair ascent and found that age was a weak but significant predictor of speed in this task as well ( 113 ). Other options that were considered as strength assessments, such as pressure-sensing chew toys ( 134 ), or systems that measure the strength with which a dog can pull against a measurement device ( 135 , 136 ), are expensive, have limited availability, depend upon the dog’s training and interest, or some combination of those flaws. The DAP FIDo will use timed stair ascent as our measurement of canine strength.…”
Section: Dog Aging Project Proposed Frailty Instrument For Dogsmentioning
confidence: 99%
“…Preliminary evidence supports a link between cardiac dysfunction and markers of chronic inflammation in dogs ( 123 ). An ongoing, longitudinal research project in aging sled dogs is investigating relationships between steady state circulating cytokines and several functional parameters related to general health, physical fitness, and cognition ( 130 ). This and future research should help elucidate the links between aging, chronic inflammation, and age-associated disease in dogs.…”
Section: Canine Geriatric Syndromementioning
confidence: 99%